2017
DOI: 10.2131/jts.42.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced food intake for 4 weeks on physiological parameters in toxicity studies in dogs

Abstract: -This study sought to clarify the effects of reduced feeding on physiological parameters in dogs to enable appropriate evaluations of the safety and toxicity of test compounds. We measured alkaline phosphatase isozymes and the circulating blood volume, as well as clinical signs, body weight, hematology, blood chemistry, electrocardiography, organ weight, and histopathology, in male beagle dogs fed a diet consisting of 300 g/day or 150 g/day for 4 weeks. There were no abnormal clinical signs in any of the dogs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Kvidera et al ( 2017a ) reported no effects on leucocyte counts in mid-lactation Holsteins following 5 days of feed restriction at 60 and 80% of ad lib intake. However, reduced feeding of rats and dogs to 50–75% of normal intake for 7–14 days was associated with a downward trend in total WBC and neutrophil counts and reduced cellularity in bone marrow (Levin et al 1993 ; Moriyama et al 2008 ; Morita et al 2017 ). Furthermore, short- and long-term caloric restrictions of humans and in rodent models have consistently shown reduced numbers of peripheral leucocytes and relocation of some subpopulations to the bone marrow (reviewed Lee and Dixit 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kvidera et al ( 2017a ) reported no effects on leucocyte counts in mid-lactation Holsteins following 5 days of feed restriction at 60 and 80% of ad lib intake. However, reduced feeding of rats and dogs to 50–75% of normal intake for 7–14 days was associated with a downward trend in total WBC and neutrophil counts and reduced cellularity in bone marrow (Levin et al 1993 ; Moriyama et al 2008 ; Morita et al 2017 ). Furthermore, short- and long-term caloric restrictions of humans and in rodent models have consistently shown reduced numbers of peripheral leucocytes and relocation of some subpopulations to the bone marrow (reviewed Lee and Dixit 2020 ).…”
Section: Discussionmentioning
confidence: 99%